Temephos Resistance in Prevention of Dengue Cases: Literature Review - ekha rifki fauzi; Kamonthip Doungjan (Universitas Nahdlatul Ulama Surabaya, 2023)
Dengue is an acute disease caused by bites from the Aedes aegypti mosquito. The decrease in the rate of dengue cases is due to the control of larval vectors using larvicide intervention. But overuse can result in resistant vectors. Temephos is a larvicide that has been circulating and used by the community for a long time. Aedes aegypti larvae are reported to be resistant in many countries. This study aims to find out the level of resistance of Aedes aegypti larvae to temephos. Scientific article searches in several databases using keywords in the period 2018-2022. This research uses the literature review method by searching articles from indexed journals as a source of information. Results from the synthesis of literature review found that temephos has experienced resistance in several countries, including Indonesia. The WHO standard for temephos of about 0.02 mg/L has experienced death resistance to the larvae of the Aedes aegypti mosquito. Resistance occurs due to the concentration of temephos used by the community for the control of dengue larvae.  The results of studies with a concentration of 1% temephos have occurred mortality larvae dengue resistance. So that the concentration level of temephos use has had a resistance impact on the control of dengue cases in various countries.